Changes in Echocardiographic Parameters According to the Rate of Residual Renal Function Decline in Incident Peritoneal Dialysis Patients. Issue 7 (February 2015) - Koo, Hyang Mo; Doh, Fa Mee; Kim, Chan Ho; Lee, Mi Jung; Kim, Eun Jin; Han, Jae Hyun; Han, Ji Suk; Ryu, Dong-Ryeol; Oh, Hyung Jung; Park, Jung Tak; Han, Seung Hyeok; Yoo, Tae-Hyun; et al.
Abstract : Abstract: Residual renal function (RRF) is associated with left ventricular (LV) hypertrophy as well as all-cause and cardiovascular (CV) mortality in patients with end-stage renal disease. However, no studies have yet examined the serial changes in echocardiographic findings according to the rate of RRF decline in incident dialysis patients. A total of 81 patients who started peritoneal dialysis (PD) between 2005 and 2012 at Yonsei University Health System, Seoul, South Korea, and who underwent baseline and follow-up echocardiography within the first year of PD were recruited. Patients were dichotomized into "faster" and "slower" RRF decline groups according to the median values of RRF decline slope (−1.60 mL/min/y/1.73 m 2 ). Baseline RRF and echocardiographic parameters were comparable between the 2 groups. During the first year of PD, there were no significant changes in LV end-diastolic volume index (LVEDVI), left atrial volume index (LAVI), or LV mass index (LVMI) in the "faster" RRT decline group, while these indices decreased in the "slower" RRT decline group. The rate of RRF decline was a significant determinant of 1-year changes in LVEDVI, LAVI, and LVMI. The linear mixed model further confirmed that there were significant differences in the changes in LVEDVI, LAVI, and LVMI between the 2 groups ( P  = 0.047, 0.048, and 0.001, respectively). During a mean follow-up duration of 31.9 months, 4 (4.9%) patients died. Compared with the "slower" RRF decline group, CV composite (20.29/100 vs 7.18/100 patient-years [PY], P  = 0.098), technique failure (18.80/100 vs 4.19/100 PY, P  = 0.006), and PD peritonitis (15.73/100 vs 4.95/100 PY, P  = 0.064) developed more frequently in patients with "faster" RRF decline rate. On multivariate Cox regression analysis, patients with "faster" RRF decline rate showed 4.82-, 4.44-, and 7.37-fold higher risks, respectively, for each clinical outcome. Preservation of RRF is important for conserving cardiac performance, resulting in an improvement in clinical outcomes of incident PD patients. Abstract : Supplemental Digital Content is available in the text